2016
DOI: 10.1016/j.bone.2015.12.054
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorders, menstrual dysfunction, weight change and DMPA use predict bone density change in college-aged women

Abstract: On average, BMD may modestly increase in college-aged women, in the absence of risk factors. However, risk factors including subclinical eating disorders, weight loss, menstrual dysfunction and DMPA use can have significant detrimental effects on BMD in young healthy physically active women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…In the research included in this study, Yang et al (2010) explained that BMD among female dancers was relatively high, probably caused by high levels of weight-bearing physical activity. Whether they involving athletes or sedentary individuals, a positive correlation between MD and low BMD was indicated in previous (Øyen, Torstveit, & Sundgot-Borgen, 2009) and in current studies (Rauh et al, 2014;Melin et al, 2015;Nieves et al, 2016) and EA and low BMD (Nieves et al, 2016;Thralls et al, 2016). But, in their research Øyen et al (2009) reported that women with < 5th percentile BMI were nine times more likely to report MD and have low BMD, and SF significantly correlated with athletes (p<.001).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In the research included in this study, Yang et al (2010) explained that BMD among female dancers was relatively high, probably caused by high levels of weight-bearing physical activity. Whether they involving athletes or sedentary individuals, a positive correlation between MD and low BMD was indicated in previous (Øyen, Torstveit, & Sundgot-Borgen, 2009) and in current studies (Rauh et al, 2014;Melin et al, 2015;Nieves et al, 2016) and EA and low BMD (Nieves et al, 2016;Thralls et al, 2016). But, in their research Øyen et al (2009) reported that women with < 5th percentile BMI were nine times more likely to report MD and have low BMD, and SF significantly correlated with athletes (p<.001).…”
Section: Discussionsupporting
confidence: 72%
“…Genderwise, females were the most represented group, with 17 studies including only female participants and three including both sexes (Cosman et al, 2013;Tenforde, Fredericson, Sayres, Cutti & Sainani, 2015;Brook et al, 2019). All the participants belonged to a healthy and active group of people, all of which took part in some sport activities, recreational, national or professional (Hoch et al, 2011;Movaseghi et al, 2012;Ackerman et al, 2015;Melin et al, 2015;Prather et al, 2016;Brook et al, 2019), competitive (Barrack et al, 2014), high school and collegiate athletes (Yang et al, 2010;Rauh, Nichols, & Barrack, 2010;Brown et al, 2014;Thralls, Nichols, Barrack, Kern, & Rauh, 2016;Tenforde et al, 2017;Tenforde et al, 2018) and military organization athletes (Cosman et al, 2013;Nieves et al, 2016) in the following sports: endurance running (Rauh et al, 2014;Duckham, Brooke-Wavell, Summers, Cameron, & Peirce, 2015;Melin et al, 2015), dance (Yang et al, 2010;Hoch et al, 2011;Tosi et al, 2019), soccer (Prather et al, 2016). The amount of BMI ranges from ≤17.5 in the study Brook et al (2019) to 25±3 in the study Cosman et al (2013).…”
Section: Resultsmentioning
confidence: 99%
“…If PBM is not achieved, this cannot be compensated for in later life. Genetics remain the largest predictor of PBM, but LEA, hypoestrogenism, menstrual dysfunction, poor calcium intake, significant weight loss, subclinical eating disorders and depot-medroxyprogesterone acetate (DMPA) contraception use can prevent an individual from reaching this genetically determined PBM [51][52][53][54]. Physical activity that involves high impact activity in adolescence is well recognised as having positive effects on BMD [55] but only in the presence of energy balance.…”
Section: Bone Mineral Density (Bmd) and Achieving Peak Bone Mass (Pbm)mentioning
confidence: 99%
“…These contraceptives not only have important health benefits, including contraceptive and no contraceptive benefits, but also have some health risks, such as bone health, particularly in reference to the use of depot medroxyprogesterone acetate (DMPA) [3]. There are publications discussion that get declines in various Bone Mass Density measurements in women beginning use of DMPA for the first time [4], with potential detrimental effects on adolescent bone mass accrual only occurring when DMPA was used for greater than 12 months [5]. However, other studies have not been able to confirm this [6], with systematic review showing that after cessation of DMPA, BMD will normal again as early as 24 weeks after cessation [7].…”
Section: Introductionmentioning
confidence: 99%